Assesment of design ligthing in outdoor stadiums / Muhd Shamshiruddin Ismail - Ismail, Muhd Shamshiruddin (Faculty of Architecture, Planning and Surveying, 2013)
A stadium, a venue that every team competed often an issue every time a new season comes. In Malaysia have more than 30 stadiums built for football match, but only 7 stadiums have permission from FAM use for night match. This problem is caused by a lack of floodlights in Lux at stadiums. Because of that, many stadiums in Malaysia cannot be used for matches at night. The research will be carried out is to identify the assessment of design of lighting in an outdoor stadium with following guideline from the Football Association of Malaysia (FAM) and Federation International of Football Association (FIFA). From this research it will reach the objective to specify criteria for a good lighting condition of the stadium, to study the comparison between Lux of the stadium and to recommend the most suitable design for lighting in stadiums in Malaysia. The study will be focused on outdoor stadium such as Stadium Perbandaran Subang Jaya and Stadium Perbandanan Kemajuan Negeri Selangor at Kelana Jaya. The method will be used to identify the problem at every stadium is observation and Lux Meter Test. From that test it will be get the criteria, specification and characteristic in good lighting of the stadium.